Adjuvant bevacizumab for melanoma patients at high risk of recurrence: survival analysis of the AVAST-M trial. (13th July 2018) - Corrie, P G; Marshall, A; Nathan, P D; Lorigan, P; Gore, M; Tahir, S; Faust, G; Kelly, C G; Marples, M; Danson, S J; Marshall, E; Houston, S J; et al.
Abstract: Background: Bevacizumab is a recombinant humanised monoclonal antibody to vascular endothelial growth factor shown to improve survival in advanced solid cancers. We evaluated the role of adjuvant bevacizumab in melanoma patients at high risk of recurrence. Patients and methods: Patients with resected AJCC stage IIB, IIC and III cutaneous melanoma were randomised to receive either adjuvant bevacizumab (7.5 mg/kg i.v. 3 weekly for 1 year) or standard observation. The primary end point was detection of an 8% difference in 5-year overall survival (OS) rate; secondary end points included disease-free interval (DFI) and distant metastasis-free interval (DMFI). Tumour and blood were analysed for prognostic and predictive markers. Results: Patients ( n =1343) recruited between 2007 and 2012 were predominantly stage III (73%), with median age 56 years (range 18–88 years). With 6.4-year median follow-up, 515 (38%) patients had died [254 (38%) bevacizumab; 261 (39%) observation]; 707 (53%) patients had disease recurrence [336 (50%) bevacizumab, 371 (55%) observation]. OS at 5 years was 64% for both groups [hazard ratio (HR) 0.98; 95% confidence interval (CI) 0.82–1.16, P = 0.78). At 5 years, 51% were disease free on bevacizumab versus 45% on observation (HR 0.85; 95% CI 0.74–0.99, P = 0.03), 58% were distant metastasis free on bevacizumab versus 54% on observation (HR 0.91; 95% CI 0.78–1.07, P = 0.25). Forty four percent of 682 melanomas assessed had a BRAF V600 mutation. In the observation arm, BRAF mutant patients had a trend towards poorer OS compared with BRAF wild-type patients ( P = 0.06). BRAF mutation positivity trended towards better OS with bevacizumab ( P = 0.21). Conclusions: Adjuvant bevacizumab after resection of high-risk melanoma improves DFI, but not OS. BRAF mutation status may predict for poorer OS untreated and potential benefit from bevacizumab. Clinical Trial Information: ISRCTN 81261306; EudraCT Number: 2006-005505-64